Metaphor in the Declaration of Independence of the United States . M.A Thesis Linguistics: 60 22 15 - Nguyễn, Thị Thanh Bình (University of Languages and International Studies, 2017)
This paper investigates typical conceptual metaphors used in the Declaration of Independence of USA by Thomas Jefferson, the USA president. Metaphor is traditionally treated as rhetoric device in poetics. However, according to cognitivists, metaphor is not (...)